2012
DOI: 10.1007/s00125-012-2554-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acetyl-CoA carboxylase 2 enhances skeletal muscle fatty acid oxidation and improves whole-body glucose homeostasis in db/db mice

Abstract: In conclusion, the ACC2-selective inhibitor (S)-9c revealed glucose-lowering effects in a mouse model of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Furthermore, ND-630 did not increase hyperglycemia in prediabetic ZDF rats relative to vehicle-treated animals and did not exacerbate the hyperglycemia of overtly diabetic animals but instead improved GSIS and reduced HbA1c levels in these animals. This effect, which also has been reported in db/db mice treated with (S)-9c (30), is suggestive of β-cell preservation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, ND-630 did not increase hyperglycemia in prediabetic ZDF rats relative to vehicle-treated animals and did not exacerbate the hyperglycemia of overtly diabetic animals but instead improved GSIS and reduced HbA1c levels in these animals. This effect, which also has been reported in db/db mice treated with (S)-9c (30), is suggestive of β-cell preservation.…”
Section: Discussionsupporting
confidence: 82%
“…A large number of isozyme-nonselective ACC inhibitors have been identified that interfere directly with ACC catalysis through interaction within the CT domain of the enzyme and have been shown to be potent in vitro and efficacious in vivo (1,9,19,(27)(28)(29)(30). Indeed, in early clinical trials one such inhibitor recently has been shown to reduce FASyn and to stimulate FAOxn after a single oral dose (29).…”
mentioning
confidence: 99%
“…However, knockout of genes that control important metabolic regulators may lead to compensatory antenatal changes affecting appetite; thus, the knockout does not always have the same effects as inhibition of the corresponding metabolic regulators in adults. For example, deletion of the gene for acetyl CoA carboxylase 2 did not improve glucose homeostasis in db / db mice , but a small‐molecule acetyl CoA carboxylase 2 inhibitor has been reported to do so . Acetyl CoA carboxylase 2 is a key regulator of fatty acid oxidation, but adaptation during fetal development and/or early life may compensate for reduced hunger signalling to the brain in acetyl CoA carboxylase 2 null mice.…”
Section: The Role Of Cannabinoid Receptors In Fatty Livermentioning
confidence: 99%
“…Insulin resistance, one of the hallmarks of metabolic syndrome, is strongly associated with elevated levels of free FAs [3]. It has been argued that an imbalance between cellular FA uptake and oxidation leads to accumulation of FAs and other lipid molecules in the cytosol, which in turn causes insulin resistance [4], [5]. Others showed that a functioning acyl-CoA uptake into mitochondria is needed to develop insulin resistance, leading to the hypothesis that intermediates of FA β-oxidation are part of the problem [6].…”
Section: Introductionmentioning
confidence: 99%